2019
DOI: 10.1089/thy.2018.0275
|View full text |Cite
|
Sign up to set email alerts
|

National Trends in Incidence, Mortality, and Clinical Outcomes of Patients Hospitalized for Thyrotoxicosis With and Without Thyroid Storm in the United States, 2004–2013

Abstract: Background: Current evidence on the incidence and outcomes of patients with thyroid storm in the United States is limited to single-center case series. This study determined the national incidence of thyrotoxicosis with and without thyroid storm and clinical outcomes among hospitalized patients during a 10-year period in the United States. Methods: Retrospective longitudinal analysis was conducted of clinical characteristics, mortality, hospital length of stay, and costs from 2004 to 2013. Adults (‡18 years of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
88
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 17 publications
(36 reference statements)
3
88
0
1
Order By: Relevance
“…In national researches from the United States and Japan, the incidence of thyroid storm was 0.57 to 0.76 and 0.20 per 100,000 persons per year, respectively [7][8]. Although thyroid storms may arise in patients with longstanding untreated hyperthyroidism, they are often precipitated by an acute underlying event.…”
Section: Figure 2: Flowchartmentioning
confidence: 99%
“…In national researches from the United States and Japan, the incidence of thyroid storm was 0.57 to 0.76 and 0.20 per 100,000 persons per year, respectively [7][8]. Although thyroid storms may arise in patients with longstanding untreated hyperthyroidism, they are often precipitated by an acute underlying event.…”
Section: Figure 2: Flowchartmentioning
confidence: 99%
“…Thyroid storm can be triggered by an acute event or trauma, such as surgery involving the thyroid or other areas, infection, and parturition [1][2][3]. Among the various precipitating factors, a recent study showed that irregular use or discontinuation of antithyroid drugs is the most common factor [3].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of thyroid storm was 0.20-0.76/100, 000 persons per year, with 4.8-5.6/100,000 hospitalized patients per year [2,3]. In a United States survey, 16% of inpatients with thyrotoxicosis were diagnosed with thyroid storm, which was associated with a significantly higher mortality rate than that in patients with thyrotoxicosis without thyroid storm [2]. Thyroid storm may be precipitated due to the irregular use or discontinuation of antithyroid medication and an acute event such as thyroid or nonthyroidal surgery or infection, especially of the upper respiratory tract [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations